2011
DOI: 10.1038/bjc.2011.401
|View full text |Cite
|
Sign up to set email alerts
|

miRNA profiling in metastatic renal cell carcinoma reveals a tumour-suppressor effect for miR-215

Abstract: Background:Renal cell carcinoma (RCC) is the most common neoplasm of the adult kidney. Metastatic RCC is difficult to treat. The 5-year survival rate for metastatic RCC is ⩽10%. Recently, microRNAs (miRNAs) have been shown to have a role in cancer metastasis and potential as prognostic biomarkers in cancer.Method:We performed a miRNA microarray to identify a miRNA signature characteristic of metastatic compared with primary RCCs. We validated our results by quantitative real-time PCR. We performed experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
102
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(112 citation statements)
references
References 44 publications
7
102
1
2
Order By: Relevance
“…Finally, we provide the first demonstration that ANKHD1 mRNA and protein are significantly enhanced in human ccRCC when compared to control, and may play an important role, in human ccRCC. (6,(26)(27)(28)(29)(30)(31), a finding that correlates with the upregulation of ANKHD1, demonstrated here. Furthermore, given that single inhibition of miRNA-29a is sufficient to restore the proliferation of RCC cells lacking ANKHD1, we suggest that miR-29a-targeted genes are likely to be responsible for the ANKHD1-mediated proliferation of ccRCCs.…”
Section: Discussionsupporting
confidence: 53%
“…Finally, we provide the first demonstration that ANKHD1 mRNA and protein are significantly enhanced in human ccRCC when compared to control, and may play an important role, in human ccRCC. (6,(26)(27)(28)(29)(30)(31), a finding that correlates with the upregulation of ANKHD1, demonstrated here. Furthermore, given that single inhibition of miRNA-29a is sufficient to restore the proliferation of RCC cells lacking ANKHD1, we suggest that miR-29a-targeted genes are likely to be responsible for the ANKHD1-mediated proliferation of ccRCCs.…”
Section: Discussionsupporting
confidence: 53%
“…miR-215 is upregulated in cervical cancer , hepatocellular carcinoma , gastric cancer (Deng et al, 2014), and prostate cancer (Walter et al, 2013), and it acts as a potential oncogene in these tumors. On the contrary, the expression of miR-215 was found to be significantly decreased in esophageal adenocarcinoma (Wijnhoven et al, 2010), colon cancer (Karaayvaz et al, 2011), and renal cell carcinoma (RCC) (White et al, 2011), where it acts as a candidate tumor suppressor. However, the correlation between miR-215 dysregulation and clinicopathological characteristics of pancreatic cancer has not yet been evaluated, and the biological roles of miR-215 and its direct functional targets in pancreatic cancer remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The miRNA-target prediction revealed that these three genes were direct targets of these miRNAs. Low expression of miR128, but not miR502-5p or miR-215/625 [14], significantly correlated with poor patient OS in both the training set and the validation sets, which is consistent with other reports for breast and colon cancers [15,16]. Moreover, patients with higher expression of CCND1 and lower expression of miR-502-5p had significantly poorer OS than did patients with lower CCND1 expression and higher miR502-5p expression.…”
Section: Discussionsupporting
confidence: 81%